Motion Analysis in Lumbar Spinal Stenosis With Degenerative Spondylolisthesis: A Feasibility Study of the 3DCT Technique Comparing Laminectomy Versus Bilateral Laminotomy. Issue 8 (October 2018) - Försth, Peter; Svedmark, Per; Noz, Marilyn E.; Maguire, Gerald Q.; Zeleznik, Mike P.; Sandén, Bengt
Abstract : Study Design: This was a randomized radiologic biomechanical pilot study in vivo. Objective: The objectives of this study was to evaluate if 3-dimensional computed tomography is a feasible tool in motion analyses of the lumbar spine and to study if preservation of segmental midline structures offers less postoperative instability compared with central decompression in patients with lumbar spinal stenosis with degenerative spondylolisthesis. Summary of Background Data: The role of segmental instability after decompression is controversial. Validated techniques for biomechanical evaluation of segmental motion in human live subjects are lacking. Methods: In total, 23 patients (mean age, 68 y) with typical symptoms and magnetic resonance imaging findings of spinal stenosis with degenerative spondylolisthesis (>3 mm) in 1 or 2 adjacent lumbar levels from L3 to L5 were included. They were randomized to either laminectomy (LE) or bilateral laminotomy (LT) (preservation of the midline structures). Documentation of segmental motion was made preoperatively and 6 months postoperatively with CT in provoked flexion and extension. Analyses of movements were performed with validated software. The accuracy for this method is 0.6 mm in translation and 1 degree in rotation. Patient-reported outcome measures were collected from the Swespine register preoperatively and 2-year postoperatively. Results: The mean preoperative values for 3D rotation and translation were 6.2 degrees and 1.8 mm. The mean increase in 3D rotation 6 months after surgery was 0.25 degrees after LT and 0.7 degrees after LE ( P =0.79) while the mean increase in 3D translation was 0.15 mm after LT and 1.1 mm after LE ( P =0.42). Both surgeries demonstrated significant improvement in patient-reported outcome measures 2 years postoperatively. Conclusions: The 3D computed tomography technique proved to be a feasible tool in the evaluation of segmental motion in this group of older patients. There was negligible increase in segmental motion after decompressive surgery. LE with removal of the midline structures did not create a greater instability compared with when these structures were preserved.